PaO2 / FiO2 ratio responsiveness to prone positioning in intubated patients with severe COVID‐19: a retrospective observational study. Issue 1 (4th June 2022) - Kawakami, Akiko; Yamakawa, Kazuma; Nishioka, Daisuke; Ota, Koshi; Kusaka, Yusuke; Umegaki, Osamu; Ito, Yuri; Takasu, Akira
Abstract : Aim: Prone positioning of coronavirus disease 2019 (COVID‐19) patients could improve oxygenation. However, clinical data on prone positioning of intubated COVID‐19 patients are limited. We investigated trends of PaO2 / FiO2 ratio values in patients during prone positioning to identify a predictive factor for early detection of patients requiring advanced therapeutic intervention such as extracorporeal membrane oxygenation (ECMO). Methods: This retrospective, observational cohort study was undertaken between April 2020 and May 2021 in a tertiary referral hospital for COVID‐19 in Osaka, Japan. We included intubated adult COVID‐19 patients treated with prone positioning within the first 72 h of admission to the intensive care unit and followed them until hospital discharge or death. Primary outcomes were in‐hospital mortality and escalation of care to ECMO. We used unsupervised k‐means clustering modeling to categorize COVID‐19 patients by PaO2 / FiO2 ratio responsiveness to prone positioning. Results: The final study cohort comprised 54 of 155 consecutive severe COVID‐19 patients. Three clusters were generated according to trends in PaO2 / FiO2 ratios during prone positioning (cluster A, n = 16; cluster B, n = 24; cluster C, n = 14). Baseline characteristics of all clusters were almost similar. Cluster A (no increase in PaO2 / FiO2 ratio during prone positioning) had a significantly higher proportion of patients placed on ECMO or who died (6/16, 37.5%). Numbers of patients with ECMO and with in‐hospital death were significantly different between the three groups ( p = 0.017). Conclusion: In Japanese patients intubated due to COVID‐19, clinicians should consider earlier escalation of treatment, such as facility transfer or ECMO, if the PaO2 / FiO2 ratio does not increase during initial prone positioning. Abstract : By using an unsupervised k‐means clustering model, we revealed the specific COVID‐19 patient cluster whose PaO2/FiO2 ratio did not increase during prone positioning and had a significantly higher proportion of patients who were placed on ECMO or died. In Japanese patients intubated due to COVID‐19, clinicians should consider earlier escalation of treatment such as facility transfer or ECMO if PaO2/FiO2 ratio does not increase during initial prone positioning.